An elderly patient with Alzheimer's disease, normal pressure hydrocephalus and traumatic brain injury: presented with behavioral symptoms similar to behavioral variant frontotemporal dementia. (3rd June 2019) - Ates Bulut, Esra; Karabay, Nuri; Soysal, Pinar; Isik, Ahmet Turan
ABSTRACT: Objective: Traumatic brain injury (TBI) is nondegenerative insult to brain from external mechanical forces. It may cause cognitive impairment, psychological problems in the long period. Besides traumatic brain injury also induces neuroinflammation and neurodegeneration process, and increases risk of dementia. It may cause various psychiatric complications such as depression, posttraumatic stress disorder, generalized anxiety disorder, and other cognitive and behavioral sequela according to site of involvement in the brain. Methods: We report a patient who has behavioral symptoms, amnesia and gait apraxy after TBI. Patient's symptoms were similar to behavioral variant Frontotemporal Dementia (bv FTD). Results: After detailed neurocognitive and radiologic evaluation he was diagnosed with Normal Pressure Hydrocephalus (NPH), and Alzheimer's Disease (AD) following TBI. Conclusion: Comprehensive geriatric assessment, including detailed radiological examinations, if it is necessary, is recommended for the optimum management of elderly patients with cognitive and psychosocial problems in order to avoid misdiagnosis and inappropriate treatment.